The Effect of E-WOM on Instagram on Visiting Interest and Impact on Visiting Decision to the Culinary Tourism Area of Pasar Lama, Tangerang - Then, Julita; Felisa, Holly (International Journal of Social and Management Studies, 2021)
One of the tourism potentials in Tangerang City which is quite famous for the Pasar Lama Culinary Area. This area is one of the tourist destinations visited by many people for culinary tourism purposes, shopping and others. Electronic Word of Mouth (E-WOM) is the development of Word-of-Mouth communication in utilizing the internet which is believed to be able to influence the interests and decisions of visiting other people. Instagram, as an internet social media that can make it easier for businesspeople to provide information, then for the public it can also make it easier to share information with potential visitors, including sharing their culinary tourism experiences. The research method used in this research is explanatory research with a quantitative approach. With purposive sampling technique, the number of samples in this study were 120 samples collected online and with instrument testing and data processing in this study resulted that there was a significant influence on Electronic Word of Mouth on visiting interest and visiting decisions on Tourist Area Visitors. Culinary Pasar Lama, Tangerang partially or simultaneously. This research is expected to provide benefits for tourism businesses in the use of Instagram social media with electronic Word of Mouth in sharing information with potential visitors to be able to attract interest and decision to visit.